1969
DOI: 10.2466/pr0.1969.25.2.399
|View full text |Cite
|
Sign up to set email alerts
|

Factor Analytic Study of Social Behavior in Children

Abstract: The purpose was to use adult participant observers to create a scale for assessing some salient personality variables of children and young adolescents living together in close quarters. The 91 children were summer campers of both sexes (8 to 15 yr.). Counselors of these children were the adult participant observers. At least two counselors rated each camper on a 49-item rating scale. Interrater reliability was determined and composite ratings of the campers were factor analyzed. Seven factors accounted for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Somewhat in opposition to the evidence just previously cited, are the results of a study by Friedman (1969). He found that children, ages 7-9» were more conforming and cooperating than were children between the ages of 10 and 12 years.…”
Section: Analyses Of Differences By Age Group For Behavioral Categorimentioning
confidence: 79%
“…Somewhat in opposition to the evidence just previously cited, are the results of a study by Friedman (1969). He found that children, ages 7-9» were more conforming and cooperating than were children between the ages of 10 and 12 years.…”
Section: Analyses Of Differences By Age Group For Behavioral Categorimentioning
confidence: 79%
“…A factor analytic study of social behavior In children of both sexes between the ages of 8 and 15 years was based on observations by counselors of like-sex in a camp situation (Friedman, 1969). Of the factors that were defined, males were rated higher on conformity-cooperation, leadershippopularity, autonomy, and conventionality than were females.…”
Section: Characteristic Traits and Behaviors Of Children In Middle Chmentioning
confidence: 99%